Modélisation d’un processus d’évaluation des compétences qui prend en compte le savoir-être et s’appuie sur le jugement professionnel - Beauchamp, Marie; Lakhal, Sawsen (Canadian Journal of Education/Revue canadienne de l'éducation, 2025)
The assessment of soft skills assessment is a challenge for teaching teams in higher education, particularly during internships in technical training programs. To adapt to an ever-changing and increasingly demanding job market (Bellier, 2004; Faure, 2023), innovative practices are emerging in the field. However, these practices present various difficulties for teaching teams: defining the concept of soft skills (which is polysemic), understanding the job market’s expectations regarding these skills, and using professional judgement to assess professional competencies by taking soft skills into account. An action-research-training project (Guay et al., 2016) was conducted with a team of six teachers from a college-level program related to the health care sector. Preceded by a training needs analysis (Roussel, 2011), the establishment of a learning community as a support system (Savoie-Zajc, 2010) aimed to put into practice a skills assessment process that considers soft skills and is based on professional judgement (Beauchamp, 2020). This article aims to present a model for documenting soft skills development during internships to support professional judgement regarding the achievement of the expected level of skills development.